Pharmaceutical Dosing Errors at a Pediatric HIV Clinic in Mwanza, Tanzania. Issue 10 (October 2017) - Naik, Neel Mahesh; Mbwanji, Ruth Nicholas; Mgawe, Mwajuma; Ongoa, Richard; Gesase, Anthony E.; Schutze, Gordon E.; Minde, Mercy; Mwita, Lumumba Francis
Abstract : The outpatient medication dosing error rate at a pediatric HIV clinic in Mwanza, Tanzania, was about 1 in every 34 prescriptions. Young children were at highest risk of a dosing error likely because of dose changes with growth and also the inconsistent supply of pediatric formulations. Majority of errors occurred at consecutive visits suggesting clinicians reordered medication without double checking dosing.